Pengaruh Pemberian Pupuk Organik Guano terhadap Pertumbuhan dan Hasil Tanaman Mentimun pada Lahan Rawa Lebak - Nurul Hasanah; Mahdiannoor; Nurul Istiqomah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
Lebak wetland can generally be used as vegetable cultivation land with proper handling. Lebak wetland land has a complex chemical problem. Giving organic material is one way to improve some soil chemical properties. The aim of this research is (i) to know the effect of guano organic fertilizer on the growth and yield of cucumber plants on lebak wetland (ii) to get the best dose of guano organic fertilizer on the growth and yield of cucumber plants on lebak wetland. The research was conducted in the Pasar Senin Village, Amuntai Tengah District, Hulu Sungai Utara Regency from May - July 2012. This study used a randomized block design (RBD), with 5 treatments and 5 replications, so there are 25 units, and each treatment there are 4 plants. Factor test in the guano organic fertilizer that g0 = 0 kg.plot-1, g2 = 0.5 kg.plot-1, g3 = 0.1 kg.plot-1, g4 = 1.5 kg.plot-1 and g5 = 2 kg.plot-1 . Results of this study showed that treatment dosing guano organic fertilizer which was highly significant on plant height ages 7, 14 and 21 DAP, number of leaves aged 7, 14 and 21 DAP, number of fruits, fruit weight and length of the fruit. The best dose of guano organic fertilizer is 10 t.ha-1 equivalent to 1 kg.plot-1 (g2).